Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/2326263x.2016.1252143
|View full text |Cite
|
Sign up to set email alerts
|

Online BCI typing using language model classifiers by ALS patients in their homes

Abstract: The P300 speller is a common brain-computer interface system that can provide a means of communication for patients with amyotrophic lateral sclerosis (ALS). Recent studies have shown that incorporating language information in signal classification can improve system performance, but they have largely been tested on healthy volunteers in a laboratory setting. The goal of this study was to demonstrate the functionality of the P300 speller system with language models when used by ALS patients in their homes. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Based on the EEG signal decoding, a few researches start to explore the non-invasive brain typing method. The approach in [33] enables ALS patients to type through BCI and achieves the typing rate of 6 characters per minute. The authors in [34] investigate three kinds of typing interfaces and illustrates that both matrix presentation and RSVP (rapid serial visual presentation) can work well.…”
Section: Related Workmentioning
confidence: 99%
“…Based on the EEG signal decoding, a few researches start to explore the non-invasive brain typing method. The approach in [33] enables ALS patients to type through BCI and achieves the typing rate of 6 characters per minute. The authors in [34] investigate three kinds of typing interfaces and illustrates that both matrix presentation and RSVP (rapid serial visual presentation) can work well.…”
Section: Related Workmentioning
confidence: 99%
“…a personal pronoun ('he') in English is more likely to precede a finite verb ('reads') than vice versa). It has been shown that predictive methods from linguistics, which rely on probabilities of co-occurrence of language units, can enhance the speed of spelling in P300 interfaces in healthy [86] and in paralyzed [87] subjects. A recent development in ECoG-BCI studies is that probabilistic n-gram-based models have been applied in production [3] and perception [88] studies to constrain the number of meaningful choices for speech decoding.…”
Section: Developments In the Area Of Direct Speech Bcis From A Linguimentioning
confidence: 99%
“…Likewise, Kubler et al showed that four individuals with ALS could learn to operate a BCI with EEG rhythms recorded over the sensorimotor cortex. However, most BCI studies in individuals with ALS have used the P300 . Of interest is the fact that most of these studies used relatively standard signal‐processing methods, in contrast to many of the studies examining archival data that tended to evaluate more novel and complex methods.…”
Section: Real‐time Applications Of Bcis With Disabled Usersmentioning
confidence: 99%